Food can't be traded: Civil society's discursive power in the context of agricultural liberalisation in India - Camile Parguel; Jean-Christophe Graz (Indian Council for Research on International Economic Relations (ICRIER), 2021)
Bilateral and regional free trade agreements increasingly substitute for the World Trade Organization in trade negotiations. Accordingly, civil society organisations opposed to trade liberalisation target this new generation of trade agreements as well. This paper examines the case of activists concerned about agricultural and food issues in India who raised their voice against the Bilateral Trade and Investment Agreement (BTIA) and the Regional Comprehensive Economic Partnership (RCEP), negotiated by India with the European Union and Asian and Oceanian countries, respectively. Among them were members of La Via Campesina - a farmer movement including 182 organisations around the world, the Right to Food Campaign - a coalition committed to the realisation of the right to food in India, and the Forum against Free Trade Agreements - a discussion platform on free trade agreements. Drawing on discourse analysis, we show that civil society actors are able to exert a diffused form of power even when they are essentially excluded from formal arenas of negotiation such as the BTIA and RCEP. They do so in particular by (1) campaigning outside the negotiating arenas, (2) framing an alternative narrative about regional trade and its implication for food, and (3) assigning new roles to participants in the policymaking process.
Keywords: F13; F52; Q17; 330; civil society actors; discourse; food security; free trade agreements; political economy